Formation of Spherical Agglomerates in Cooling Crystallization of Hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine. Issue 12 (29th September 2017) - Lee, Jae-Eun; Kim, Jae-Kyeong; Kim, Hyoun-Soo; Koo, Kee-Kahb
Abstract: The production of spherical agglomerates of hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) from acetone by cooling crystallization with poly(vinylpyrrolidone) (PVP) is described. It was found that PVP suppresses the nucleation of RDX at the initial stage, but tremendous nucleation of RDX occurred abruptly after the induction period. The rapid nucleation may be associated with the primary nucleation due to the presence of PVP. It can be concluded that the addition of PVP results in the formation of RDX particles with sufficient number density for spherical agglomeration. It was found that such spherical agglomeration propagates very rapidly after nucleation within one minute and the size of spherical agglomerates is affected by the cooling rate. Abstract : RDX by cooling crystallization from acetone was demonstrated. A proposed mechanism for this process is an extremely rapid nucleation induced due to primary nucleation by a polymeric additive. This rapid nucleation provides a high enough number density of particles for the formation of spherical agglomerates.